Relation between depression after stroke, antidepressant therapy, and functional recovery. Issue 2 (1st August 2001) - Gainotti, G; Antonucci, G; Marra, C; Paolucci, S
Abstract : The aim was to evaluate the effects of poststroke depression and antidepressant therapy on the improvement of motor scores and disability, to verify if the negative effects of poststroke depression on functional recovery could be counterbalanced by taking antidepressant drugs. RESULTS OBTAINED BEFORE, DURING, AND AFTER REHABILITATION : on the Barthel index, Canadian neurological scale, and Rivermead mobility index—by 49 depressed patients with stroke, who had been treated (n=25) or not treated (n=24) according to the different therapeutic approaches of their physicians, were compared with results similarly obtained by 15 non-depressed patients with stroke. Analysis was by multivariate analysis of variance for repeated measures There was a non-significant difference between the groups in their motor and functional scores, and a significant improvement on time. A significant interaction between group and time was seen. This interaction was particularly significant on the Rivermead mobility index, and was due to the fact that the recovery of non-treated depressed patients with stroke was less than the non-depressed and the depressed but treated patients with stroke. Furthermore, recovery from depression was significantly greater in treated than in non-treated depressed patients with stroke. In conclusion, poststroke depression has negative effects on functional recovery, and a pharmacological treatment of depression can counterbalance this effect.